Development Strategy for Asol Water Tourism in Oma Village, Haruku Island, Central Maluku - Siahaya, Marizol; Rehatta, Geradin; Wairisal, Paulus Liberthy (JENDELA PENGETAHUAN, 2024)
This study explores the entrepreneurial potential of students in the Faculty of Education at Pattimura University, particularly in the Department of Social Sciences. Data were collected through the distribution of questionnaires to 99 students, considering their academic year, gender, and department/program of study. Descriptive statistical analysis provided an empirical overview of students' entrepreneurial potential. The research findings indicate that students' entrepreneurial potential significantly influences entrepreneurship skills development. The analysis of questionnaire scores was conducted using a weighted average based on relative load factors. The implications of this research suggest that enhancing and developing students' entrepreneurial potential can contribute positively to the operational aspects and success of student entrepreneurship. Students with entrepreneurial characteristics are expected to possess competencies that support the creation of business plans.